Factors Influencing the Students’ Acceptance of E-Learning at Teacher Education Institute: An Exploratory Study in Malaysia - Muhamad Suhaimi Taat; Agatha Francis (Sciedu Press, 2020)
This study aimed to identify the level of e-learning acceptance, and factors that influence it, among students at a teacher education institute in Malaysia. Factors involved in the study were usability perceptions, ease of use, lecturer characteristics, information quality, system quality, and technical support. A total number of 230 students were selected as respondents from the third- and final-year students from various undergraduate programmes that employed e-learning. The instrument used in this study consisted of a set of questionnaires containing 49 question items and using five-point Likert scales. The results of the study were analysed using descriptive statistics that derived means and standard deviations. The results show that the key factors influencing the acceptance of e-learning among the students are usability, lecturer characteristics, system quality, the information provided, and available technical support. The findings also show that students' acceptance of e-learning is influenced by the benefits and usefulness of the programme and, as well, saving time and receiving course content that is simple and appropriate to the task.